2005
DOI: 10.1002/bjs.5083
|View full text |Cite
|
Sign up to set email alerts
|

Breast-conserving surgery with resection of the nipple–areola complex for subareolar breast carcinoma

Abstract: Breast-conserving therapy is a safe and cosmetically acceptable alternative to mastectomy for subareolar breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Our study found no difference with respect to local recurrence and systemic disease in patients with retroareolar carcinoma treated by either BCS or mastectomy. These data are similar to other studies showing the oncologic safety of BCS in retroareolar breast cancers, provided postoperative radiation therapy is given (3–13,18) (Table 3). However, due to the small number of patients included in all studies and the short‐term follow‐up no final conclusions may be drawn yet on the long‐term oncologic outcome of retroareolar breast cancer treated by BCS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study found no difference with respect to local recurrence and systemic disease in patients with retroareolar carcinoma treated by either BCS or mastectomy. These data are similar to other studies showing the oncologic safety of BCS in retroareolar breast cancers, provided postoperative radiation therapy is given (3–13,18) (Table 3). However, due to the small number of patients included in all studies and the short‐term follow‐up no final conclusions may be drawn yet on the long‐term oncologic outcome of retroareolar breast cancer treated by BCS.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of local recurrence and distant metastases following breast conservation surgery (BCS) combined with radiation therapy is comparable to that after mastectomy (1,2). Although the oncologic safety of BCS has been shown in patients with retroareolar breast cancers (3–13) some surgeons still prefer a mastectomy over BCS in these patients. This may be based on personal oncologic concerns and the often poor cosmesis resulting from resection of the nipple‐areola complex (NAC) and subareolar glandular tissue (6,14–16).…”
mentioning
confidence: 99%
“…[52][53][54][55][56][57][58][59] However, there have been studies reporting BCS to be equally efficient in patients with subareolar breast cancers as compared to that in patients with peripheral breast cancers. A prospective study by Tausch et al [60] included 44 women who had suspected nipple involvement and underwent BCS with the removal of NAC. The study reported no local failure in any of the patients at 51 months and the cosmetic results were satisfactory to excellent.…”
Section: Breast Conserving Surgery In Subareolar/retroareolar Breast mentioning
confidence: 99%
“…Subareolar tumours have previously been viewed as an indication for mastectomy but may be safely approached by central excision with resection of the nipple-areola complex [54, 55]. The skin wound can be closed with a purse string or horizontal suture, although this tends to reduce the projection of the breast mound.…”
Section: Optimising Cosmesis: Central Tumours Occupying 10–20% Of mentioning
confidence: 99%